Greater Anteroposterior Default Mode Network Functional Connectivity in Long-Term Elderly Yoga Practitioners - Santaella, Danilo Forghieri; Balardin, Joana Bisol; Afonso, Rui Ferreira; Giorjiani, Giuliana Martinatti; Sato, João Ricardo; Lacerda, Shirley Silva; Amaro Jr., Edson; Lazar, Sara; Kozasa, Elisa H. (Frontiers in Aging Neuroscience, 2019)
Large-scale brain networks exhibit changes in functional connectivity during the aging process. Recent literature data suggests that Yoga and other contemplative practices may revert, at least in part, some of the aging effects in brain functional connectivity, including of the Default Mode Network (DMN). The aim of this cross-sectional investigation was to compare resting-state functional connectivity of the medial prefrontal cortex (MPFC) and posterior cingulate cortex - precuneus (PCC-Precuneus) in long-term elderly Yoga practitioners and healthy paired Yoga-naïve controls. Two paired groups: yoga (Y-20 women, Hatha Yoga practitioners; minimum twice a week of practice frequency for at least 8 years) and control group (C-20 women, Yoga-naïve, matched by age, years of formal education, and physical activity) were evaluated for: Mini Mental State Examination (MMSE), Beck Depression Inventory (BDI), Instrumental Activities of Daily Living (IADL), and open-eyes resting-state fMRI - seed to voxel connectivity analysis (CONN toolbox 17.f) with pre-processing - realignment and unwarping, slice-timing correction, segmentation, normalization, outlier detection, and spatial filtering. Analysis included a priori regions of interest (ROI) of DMN main nodes – MPFC and PCC-Precuneus. There was no difference between groups for: age, years of formal education, MMSE, BDI and IADL. Yoga group had higher correlation between MPFC and right angular gyrus, compared to controls. Elderly women with at least 8 years of yoga practice presented greater intra-network anteroposterior brain functional connectivity of the default mode network. This finding may contribute for the understanding of the influences of Yoga practice for a healthier cognitive aging process.